2007
DOI: 10.1245/s10434-006-9322-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Metastatic Lymph Node Ratio in Node-Positive Colon Carcinoma

Abstract: Ratio-based LN staging, which reflects the number of LNs examined and the quality of LN dissection, is a potent modality for prognostic stratification in patients with LN-positive colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
128
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 17 publications
19
128
0
8
Order By: Relevance
“…In gastric cancer, ratio-based nodal staging was shown to be better than number-based classification in defining stage migration [12][13][14]20]. In addition ratiobased staging has been reported to significantly predict oncologic prognosis in patients with colon cancer [16,21]. In the present study, we found also that LNR has important prognostic significance in patients with colorectal cancer.…”
Section: Discussionsupporting
confidence: 59%
“…In gastric cancer, ratio-based nodal staging was shown to be better than number-based classification in defining stage migration [12][13][14]20]. In addition ratiobased staging has been reported to significantly predict oncologic prognosis in patients with colon cancer [16,21]. In the present study, we found also that LNR has important prognostic significance in patients with colorectal cancer.…”
Section: Discussionsupporting
confidence: 59%
“…the ratio of metastatic to retrieved lymph nodes) was found to be an important independent prognostic factor in various malignancies (19)(20)(21)(22). Also in colon cancer some studies show a strong association of metastatic lymph node ratio (LNR) with disease recurrence and survival (23)(24)(25)(26). In rectal cancer the evidence is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a substantial body of literature suggests that the absolute number of lymph nodes removed, whether positive or negative, is independently correlated with survival [14,15]. Furthermore, a number of studies have examined the ratio of positive lymph nodes to total number of lymph nodes as a predictor of survival [16][17][18][19][20][21]. These studies show that the ratio of positive nodes to the total number of nodes removed and examined is more predictive of patient outcome than the number of nodes involved with tumor alone.…”
Section: Introductionmentioning
confidence: 99%